Anti-proliferative, apoptotic induction, and anti-migration effects of hemi-synthetic 1′S-1′-acetoxychavicol acetate analogs on MDA-MB-231 breast cancer cells - Liew, S.K.; Azmi, M.N.; In, L.L.A.; Awang, Khalijah; Nagoor, Noor Hasima (Dove Medical Press, 2017)
Nine analogs of 1′S-1′-acetoxychavicol acetate (ACA) were hemi-synthesized and evaluated for their anticancer activities against seven human cancer cell lines. The aim of this study was to investigate the anti-proliferative, apoptotic, and anti-migration effects of these compounds and to explore the plausible underlying mechanisms of action. We found that ACA and all nine analogs were non toxic to human mammary epithelial cells (HMECs) used as normal control cells, and only ACA, 1′-acetoxyeugenol acetate (AEA), and 1′-acetoxy-3,5-dimethoxychavicol acetate (AMCA) inhibited the growth of MDA-MB-231 breast cancer cells with a half-maximal inhibitory concentration (IC50) value of <30.0 µM based on 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay results, and were selected for further investigation. DNA fragmentation assays showed that these three compounds markedly induced apoptosis of MDA-MB-231 cells. Western blot analysis revealed increased expression levels of cleaved PARP, p53, and Bax, while decreased expression levels of Bcl-2 and Bcl-xL were seen after treatment, indicating that apoptosis was induced via the mitochondrial pathway. Moreover, ACA, AEA, and AMCA effectively inhibited the migration of MDA-MB-231 cells. They also downregulated the expression levels of pFAK/FAK and pAkt/Akt via the integrin β1-mediated signaling pathway. Collectively, ACA and its hemi-synthetic analogs, AEA and AMCA are seen as potential anticancer agents following their abilities to suppress growth, induce apoptosis, and inhibit migration of breast cancer cells.